Ana al-Haqq (Akulah kebenaran). Menyikapi teosofi al-Hallaj dalam kitab thawasin - KAMRAN, Gilani (Risalah Gusti, 2001)
Ana al-Haqq (Akulah kebenaran). Menyikapi teosofi al-Hallaj dalam kitab Thawasin